Potential relation between non-alcoholic fatty liver disease and glycemic and metabolic parameters in subjects without diabetes - H. Naguib (SpringerOpen, 2021)
Abstract Background Nonalcoholic fatty liver disease (NAFLD) is proved to be related to insulin resistance and type 2 diabetes, and it is also not rare in individuals without diabetes. The present study attempts to identify the metabolic risk factors of NAFLD among those individuals. Results ALT and HbA1c levels were independently associated with NAFLD development in individuals without diabetes. Receiver operating characteristic (ROC) analysis identified the optimal cutoff point of ALT (> 19 IU/ml) with AUC = 0.731, 95% CI 0.653–0.809. On the other hand, the optimal cutoff point of HbA1c was identified to be > 5.1% with AUC = 0.665, 95% CI 0.581–0.750. Conclusions Early identification of NAFLD among subjects without diabetes is crucial. In this study, ALT and HbA1c cutoff values had been identified, so we suggest that inclusion of both HbA1c and ALT levels may have significant implications for prediction of NAFLD among individuals without diabetes.